Nivolumab plus ipilimumab in the treatment of advanced melanoma. Issue 1 (December 2015) - Tsai, Katy; Daud, Adil
Abstract Advanced melanoma has historically been a difficult disease to treat due to few effective systemic treatment options. However, over the past few years, scientific advancements in immune checkpoint inhibition have resulted in several novel approaches that have changed front-line management of advanced melanoma. Despite these exciting developments, there remains room for improvement in treatment outcomes. Combination immunotherapy, in particular combined cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed death 1 (PD-1) blockade, represents an important first step in this direction.